2012
DOI: 10.1002/chem.201102252
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation of Aromatics with the Help of a Non‐Haem FeOOH: A Mechanistic Study under Single‐Turnover and Catalytic Conditions

Abstract: Ferric-hydroperoxo complexes have been identified as intermediates in the catalytic cycle of biological oxidants, but their role as key oxidants is still a matter of debate. Among the numerous synthetic low-spin Fe(III)(OOH) complexes characterized to date, [(L(5)(2))Fe(OOH)](2+) is the only one that has been isolated in the solid state at low temperature, which has provided a unique opportunity for inspecting its oxidizing properties under single-turnover conditions. In this report we show that [(L(5)(2))Fe(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
114
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 68 publications
9
114
1
Order By: Relevance
“…In analogous work, Banse and coworkers [20] reported aromatic hydroxylation reactions by an iron(III)-hydroperoxo species (complex 1 in Scheme 1) with the pentadentate L 5 2 ligand (N-methyl- [21,22] and found it to react with benzene and anisole substrates efficiently. Interestingly, the use of [1,3,5-D 3 ]-benzene as a substrate probe [20], evidenced the occurrence of an NIH-shift whereby a hydrogen atom from the ipso-carbon position moved to the adjacent carbon atom, with a kinetic isotope effect (KIE) of k H /k D = 1.53 ± 0.16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In analogous work, Banse and coworkers [20] reported aromatic hydroxylation reactions by an iron(III)-hydroperoxo species (complex 1 in Scheme 1) with the pentadentate L 5 2 ligand (N-methyl- [21,22] and found it to react with benzene and anisole substrates efficiently. Interestingly, the use of [1,3,5-D 3 ]-benzene as a substrate probe [20], evidenced the occurrence of an NIH-shift whereby a hydrogen atom from the ipso-carbon position moved to the adjacent carbon atom, with a kinetic isotope effect (KIE) of k H /k D = 1.53 ± 0.16.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the use of [1,3,5-D 3 ]-benzene as a substrate probe [20], evidenced the occurrence of an NIH-shift whereby a hydrogen atom from the ipso-carbon position moved to the adjacent carbon atom, with a kinetic isotope effect (KIE) of k H /k D = 1.53 ± 0.16. Using analogous oxidants with the same probe [23] similar results were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the iron-based oxidants need to be distinguished from each other and from hydroxyl radicals. In the following, we will discuss some studies that have been performed, either by using isolated powders [47,58] or by employing low temperatures in combination with stopped-flow techniques [45,62,73].…”
Section: Nucleophilic Reactions Of Iron Peroxide Adductsmentioning
confidence: 99%
“…The sole oxidant of P450 enzymes is CpdI. A range of experimental and computational studies have ruled out Cpd0 as an oxidant [17][18][19] (i.e., iron(III)-hydroperoxo), although recent studies on biomimetic nonheme iron(III)-hydroperoxo models have shown reactivity with arenes and halides [20][21][22]. These differences were assigned as resulting from differences in the O-O bond cleavage patterns between heme and nonheme iron(III)-hydroperoxo systems, where the hemes give favorable heterolytic cleavage and the nonhemes homolytic cleavage.…”
Section: Introductionmentioning
confidence: 99%